Reoffending: review of selected countries : final report for audit Scotland (Report, 2012)
This report presents research commissioned by Audit Scotland on international levels and experience of reoffending. It aims to set the Scottish experience of reoffending in context and to identify factors which other jurisdictions have seen affect reoffending rates. The jurisdictions included in this review are: Scotland, England and Wales, Northern Ireland, Ireland, Norway and New Zealand.